2014
DOI: 10.1021/ef5013038
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity and pHeResponse of Fuel Ethanol Contaminants

Abstract: Electrical conductivity and pH e are used in some parts of the world as fuel specification parameters for denatured fuel ethanol (DFE). Conductivity has been correlated with the presence of corrosive ions such as chloride, and high-conductivity fluids are more likely to cause electrochemical or galvanic corrosion. This study examined how electrical conductivity and pH e of DFE are affected by impurities, including sodium chloride (NaCl), magnesium chloride (MgCl 2 ), hydrochloric acid, magnesium sulfate (MgSO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In the case of ethanol–water mixtures, anhydrous and hydrous bioethanol fuel is required to have a solvent-specific pH (pHe) between 6.5 and 9.5 at 25.0 °C [ 17 , 33 ]. This range exists to encompass variations arising from the bioethanol production process, water content (hydrous bioethanol), and presence of additives [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of ethanol–water mixtures, anhydrous and hydrous bioethanol fuel is required to have a solvent-specific pH (pHe) between 6.5 and 9.5 at 25.0 °C [ 17 , 33 ]. This range exists to encompass variations arising from the bioethanol production process, water content (hydrous bioethanol), and presence of additives [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ethanol–water mixtures, anhydrous and hydrous bioethanol fuel is required to have a solvent-specific pH (pHe) between 6.5 and 9.5 at 25.0 °C [ 17 , 33 ]. This range exists to encompass variations arising from the bioethanol production process, water content (hydrous bioethanol), and presence of additives [ 33 ]. Further, a report of ethanol–water mixtures used in the preservation of museum collections has shown a wide dispersion in the of solutions of identical measured ethanol content [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Moreover, it has been recently shown that the conductivity of ethanol depends on the material of the beaker in which it is measured, with a conductivity varying from 2 to 250 µS/m for the same sigma-aldrich ethanol. 28 Therefore, it is logical to assume that the conductivity of ethanol mixed with toluene depends on the material of the glassware in which they have been mixed. In water, the pyrex glassware releases sodium and dihydrogenosilicate ions, 29 maybe it releases sodium and trihydrogenosilicate ions in ethanol.…”
Section: Discussion About Recent Experimental Findingsmentioning
confidence: 99%
“…Very little data on salt solubility in reagent grade ethanol or denatured ethanol meeting ASTM D4806 are available. Luecke and McCormick (2014) found sodium sulfate to be insoluble in reagent grade ethanol denatured with natural gasoline in a study of how salts affect denatured ethanol's electrical conductivity. A review of laboratory notes from that project shows that sodium sulfate solubility was no more than 0.3 ppm, and likely much lower.…”
Section: Solubility Of Various Sulfate and Sulfite Saltsmentioning
confidence: 99%